Impending aortic aneurysm rupture – a case report and review of the warning signs - David S. Gish; J. Austin Baer; Gordon S. Crabtree; Bilal Shaikh; Shoaib B. Fareedy (Journal of Community Hospital Internal Medicine Perspectives, 2016)
Abdominal aortic aneurysm (AAA) may present with subtle clinical findings. Recognition of the imaging features of an impending rupture is key for timely diagnosis. This report reviews the classic computed tomography findings of impending AAA rupture and presents a recent case which illustrates the key features.